2015
DOI: 10.5539/ijbm.v10n11p62
|View full text |Cite
|
Sign up to set email alerts
|

Gender Aware Employer Branding: How to Become Authentic, Unique and Attractive

Abstract: Despite a global financial crisis, the concept Employer Branding became the point of departure for an interactive collaboration between an engineering company and a research team. When reviewing academic literature the conclusion was that very few articles combine the concepts of employer brand and gender equality. This article contributes theoretically to promote and examine arguments for the potential of adopting a gender perspective when developing an employer brand and when compiling the employer value pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
3
0
10
Order By: Relevance
“…Alniacik and Alniacik (2012) reported significant differences in the perceptions of dimensions of employer branding between males and females. Lundkvist (2015) also highlighted the importance of adopting a gender perspective to establish a strong employer brand. Nevertheless, to the best of our knowledge, the empirical testing of the moderating effect of gender on employer branding and employee brand equity remains unexplored.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Alniacik and Alniacik (2012) reported significant differences in the perceptions of dimensions of employer branding between males and females. Lundkvist (2015) also highlighted the importance of adopting a gender perspective to establish a strong employer brand. Nevertheless, to the best of our knowledge, the empirical testing of the moderating effect of gender on employer branding and employee brand equity remains unexplored.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Understanding the importance given to employer branding factors among different demographic groups is critical for organizations to customize their employer brand strategy. Unfortunately, only limited efforts have been made to explicitly understand the difference in employer brand perceptions among different demographic groups, especially gender and years of experience, since employer brand perceptions could differ among male and female employees (Lundkvist, 2015) and among new and experienced employees (Jain and Bhatt, 2015). Although Aslan et al (2016) reported no difference among gender and employer brand perceptions, others have reported significant differences in employer branding perceptions among gender (Alnıaçık and Alnıaçık, 2012; Jain and Bhatt, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For women, gender inequality in the workplace might exert a deterring effect, which is tantamount to arguing that equality has the opposite effect. This is reflected in present-day strategies of employer branding, which place gender equality high on the agenda in order to draw women in (see Bellou, 2010; Charlesworth & Baird, 2007; Lundkvist, 2015). Given this, women’s perception of the military as an organization that has (not) been able to achieve full gender equality could be construed as part of the military’s “organizational image” among women, which should affect women’s attraction to the military as a potential employer.…”
Section: Previous Research and Theoretical Considerationsmentioning
confidence: 99%